2022
DOI: 10.1111/acel.13632
|View full text |Cite
|
Sign up to set email alerts
|

NF‐κB‐dependent secretome of senescent cells can trigger neuroendocrine transdifferentiation of breast cancer cells

Abstract: Cellular senescence is characterized by a stable proliferation arrest in response to stresses and the acquisition of a senescence‐associated secretory phenotype, called SASP, composed of numerous factors including pro‐inflammatory molecules, proteases, and growth factors. The SASP affects the environment of senescent cells, especially during aging, by inducing and modulating various phenotypes such as paracrine senescence, immune cell activity, and extracellular matrix deposition and organization, which critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Using a calcium chelator, we demonstrated that calcium activates STAT3 to promote EEC differentiation. Calcium-related signaling has previously been implicated in EEC differentiation in normal colon organoids and the Drosophila midgut, and neuroendocrine differentiation in breast and prostate cancer, suggesting that calcium signaling may generally drive neuroendocrine differentiation through STAT3 activation in normal and cancerous settings 20,[45][46][47] .…”
Section: Discussionmentioning
confidence: 99%
“…Using a calcium chelator, we demonstrated that calcium activates STAT3 to promote EEC differentiation. Calcium-related signaling has previously been implicated in EEC differentiation in normal colon organoids and the Drosophila midgut, and neuroendocrine differentiation in breast and prostate cancer, suggesting that calcium signaling may generally drive neuroendocrine differentiation through STAT3 activation in normal and cancerous settings 20,[45][46][47] .…”
Section: Discussionmentioning
confidence: 99%
“…Cytosolic Ca 2+ experiments were achieved as previously described [ 39 ]. Briefly, plated cells were loaded with the Fura2-AM dye (2.5 µM; Molecular Probes) for 30 min at 37 °C in Ca 2+ -containing buffer (HBSS; Gibco).…”
Section: Methodsmentioning
confidence: 99%
“…Of note, breast and prostate non-hormone-dependent cancer cells do not enter into senescence and NED when exposed to the SASP. Nevertheless, co-occurrence of senescence and NED and whether it is restricted or not to hormone-dependent cells will have to be confirmed in different cellular models, and whether there are some interdependencies between these two phenotypes will need to be investigated ( Raynard et al, 2022 ).…”
Section: Senescent Cells Can Display Reinforcement Establishment and ...mentioning
confidence: 99%